2010
DOI: 10.1086/652775
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Skin and Environmental Contamination with Methicillin-ResistantStaphylococcus aureusbefore Results of Polymerase Chain Reaction at Hospital Admission Become Available

Abstract: Before any contact precautions can be implemented, newly identified MRSA carriers frequently have contaminated their environment with MRSA and have contamination of commonly examined skin sites. In hospitals that perform active surveillance, strategies are needed to minimize delays in screening or to preemptively identify patients at high risk for disseminating MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…The best approach to prevent and control MRSA remains uncertain, but it is well known that MRSA is a colonizing organism for most affected patients and can be detected through active surveillance and effective screening [2] . Frequent screening of EMS personnel for MRSA infection or colonization is not recommended in the current infection control policies, but because nasally-colonized individuals contribute to the dissemination of MRSA, active surveillance systems are needed for effective and early identification of populations at high risk [8] . According to Köck et al, routine MRSA surveillance testing has medical value and cost effectiveness upon application in healthcare settings [16] .…”
Section: The Need For Surveillance Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best approach to prevent and control MRSA remains uncertain, but it is well known that MRSA is a colonizing organism for most affected patients and can be detected through active surveillance and effective screening [2] . Frequent screening of EMS personnel for MRSA infection or colonization is not recommended in the current infection control policies, but because nasally-colonized individuals contribute to the dissemination of MRSA, active surveillance systems are needed for effective and early identification of populations at high risk [8] . According to Köck et al, routine MRSA surveillance testing has medical value and cost effectiveness upon application in healthcare settings [16] .…”
Section: The Need For Surveillance Systemsmentioning
confidence: 99%
“…Also it has been proven that MRSA can contaminate surroundings and reachable objects such as keyboards, phones, stethoscopes, and ties [8][9][10] . Nonetheless, there is a significant decline of MRSA infections worldwide, albeit for unknown reasons [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Spread to the environment can be quick with 35% of colonized patients having contaminated their environment within 33 hours after admission. 5 Despite the publication of significant reductions of MRSA infections by at least 14 studies using active surveillance testing and isolation/decolonization protocols involving highrisk patients, 6,7 patients admitted to the medical intensive care unit (ICU)/neonatal ICU, 8Y12 surgical wards/patients, 9,13Y17 or the entire hospital, 18,19 active surveillance testing and isolation/decolonization have still not been widely adopted by hospitals. Two of the studies that implemented ICU active surveillance testing protocols even observed a facility-wide reduction of MRSA infections.…”
Section: Topic Review and Perspectivementioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, a previous study showed a decrease in the MRSA detection rate after the improvement of environmental cleaning/disinfection methods. [7] Therefore, in terms of MRSA infection, the disinfection of environmental surfaces such as door handles is important.…”
Section: Introductionmentioning
confidence: 97%